2014
DOI: 10.1007/s00253-014-5755-y
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric and room temperature plasma (ARTP) as a new powerful mutagenesis tool

Abstract: Developing rapid and diverse microbial mutation tool is of importance to strain modification. In this review, a new mutagenesis method for microbial mutation breeding using the radio-frequency atmospheric-pressure glow discharge (RF APGD) plasma jets is summarized. Based on the experimental study, the helium RF APGD plasma jet has been found to be able to change the DNA sequences significantly, indicating that the RF APGD plasma jet would be a powerful tool for the microbial mutagenesis with its outstanding fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
225
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 299 publications
(233 citation statements)
references
References 45 publications
1
225
0
Order By: Relevance
“…These results proved that the physiological properties of fungal spores were related to their physiological metabolic functions. Changing in the physiological characteristics of microbes via mutagenesis indicated differential secondary metabolite accumulation (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results proved that the physiological properties of fungal spores were related to their physiological metabolic functions. Changing in the physiological characteristics of microbes via mutagenesis indicated differential secondary metabolite accumulation (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Also, some new and powerful mutagenesis methods have been applied to the breeding of high-yielding industrial strains. These new methods have technological advantages (higher mutation rates and more abundant phenotypic mutations) (Hu et al, 2013;Zhang et al, 2015), and include atmospheric and room temperature plasma mutagenesis technology in Beijing (Li et al, 2008;Wang et al, 2010;Lu et al, 2011;Zhang et al, 2014) (Yang et al, 2013), as a type of high linear energy transfer (LET) irradiation, have a higher relative biological effect (RBE) compared with X-and γ-rays (Yang et al, 2007;Li S.W. et al, 2011;Ota et al, 2013;Zhou et al, 2013), and are expected to increase mutation frequency and have a wide mutation spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Physical and chemical mutagenization can also introduce site mutations or large-scale changes into coding genes, gene clusters, or their regulative areas, leading to the activation of silent genes and new secondary metabolites [3,4]. Plasma treatment, as an efficient and convenient mutagenesis method, has been widely used in industrial microbial breeding [5]. However, as for its application in microbial natural product research, especially for improving fungal chemical diversity, related reports are scarce at present.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ARTP has a higher positive genotoxic response than traditional mutation methods, making it a potentially effective mutation breeding strategy (Hua et al, 2010;Wang et al, 2010;Li et al, 2014;Zhang et al, 2014). In this study, ARTP-irradiation was used for inducing random mutations, and high AD-producing M. neoaurum mutants were selected later.…”
Section: Mutagenesis and Mutant Selectionmentioning
confidence: 99%
“…In this study, the operating parameters were as follows: the radio frequency (RF) power input was 40 W, the gas flow was 12.5 L/min, the distance between the plasma torch nozzle exit and the sample plate (D) was 1 cm, the temperature of the plasma jet was below 40 °C, and the plasma treatment time ranged from 60 to 180 s Li et al, 2014;Zhang et al, 2014).…”
Section: Mutagenesis With the Artp Biological Breeding System And Mutmentioning
confidence: 99%